Basic Histological Techniques (MicroTechniques) for Staining of Animal Tissue - Chaudhuri, Priyasankar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Background: Animal tissues when removed from the body must be well preserved in life-like manner as possible. Tissues must be further processed in graded alcohol and other essential chemicals to make them ready for studies under microscope. Aim/Objectives: To highlight the processes of handling animal tissues from the time they were removed from the body to the point they were processed, stained and made ready for microscopically diagnosis. Methodology: Standard and academic search engines were utilized and histological text consulted to review essential protocols for histological handling and processing of animal tissues and how they are stained. Basic staining techniques were included while advanced techniques were excluded. Results and Recommendation: Staining techniques such as Haematoxylin and Eosin, Weigert stain, Trichrome stain, Silver stain, Periodic acid Schiff and Wright stains were highlighted as with their staining appearance on animal tissues. Reaction of tissue components following application of dyes is given in Table 1. It is recommended that standard protocols be followed during staining of animal tissues for histological studies.